SMART 2008: Overview, synthesis and lessons learned from the International Benchmark. (1st January 2016) - Richard, Benjamin; Martinelli, Paolo; Voldoire, François; Chaudat, Thierry; Abouri, Salim; Bonfils, Nicolas
Highlights: A International Benchmark to compare seismic assessment methods was launched in 2008. A synthesis of the results is presented considering several indicators such as the floor response spectra. The main lessons and conclusions from the SMART 2008 benchmark are exposed. Abstract: This paper reports the main results and conclusions of an International Benchmark jointly organized within the framework of a wide research program launched by the French Atomic Energy and Sustainable Energies Commission (CEA), Electricité De France (EDF) entitled "Seismic design and best-estimate Methods Assessment for Reinforced concrete buildings subjected to Torsion and nonlinear effect (SMART)". This research program included first an experimental campaign on reduced scaled specimen and shaking table tests, and second, a Benchmark exercise based on the contest of numerical methods and methodologies referring to the experimental results from the tests. The objectives of the Benchmark exercise were to compare the results obtained by conventional seismic assessment methods with those obtained by best-estimate methods, to compare the methodologies of taking into account uncertainties in the numerical analyses when a probabilistic assessment should be performed and to create an event allowing the international community in earthquake engineering to discuss the aforementioned topics of common interest. According to the analysis of the results, it turned out that (a) conventional methods are clearly able to provide relevant seismic assessment at the design level; (b) when dealing with overdesign seismic loadings, advanced best-estimate methods seem to be able to capture several key indicators such as the frequency shift of the peak of the response spectra; and (c) the blind nonlinear computations demonstrate a high robustness level of the specimen based on both structural and local damage indicators (frequency shift and inter-story drift, respectively).